Wound healing activity of the flowers of Lilium candidum L. in burn wound model in rats - Saeideh Momtaz; Mahshid Dibaj; Alireza Abdollahi; Gholamreza Amin; Roodabeh Bahramsoltani; Mohammad Abdollahi; Parvin Mahdaviani; Amir Hossein Abdolghaffari (Institue of Medicinal Plants, ACECR, 2020)
Background: Ethnomedicinal plants are of interest for treatment of various wound types. Objective: This study aimed to evaluate burn wound healing potential of the hydro-alcoholic extract of the flowers of Lilium candidum L. in rats. Methods: DPPH free radical scavenging power, total flavonoids, and the phenolic content of the extract were evaluated. Following burn wound induction, 30 Wistar rats were divided into 5 groups; silver sulfadiazine cream 1% (reference standard), eucerin (control), and 5%, 10% and 20% ointments of L. candidum flowers extract (treatment groups). Wound contraction and the percentage of wound healing were measured every day until 14th day and the histological changes were evaluated. Results: DPPH assay of L. candidum extract indicated high antioxidant activity. Total phenolic content of L. candidum extract was equal to 157 mg gallic acid equivalent/g; while total flavonoid was measured as 32.4 mg quercetin equivalent/g dried extract. The mean of wound area was significantly different in three 5%, 10% and 20% extract-treated rats in comparison with the control. Although, 20% ointment of L. candidum flowers extract demonstrated the best wound healing improvement, even better than silver sulfadiazine. Histopathological analysis confirmed the wound healing activity of L. candidum and promoting tissue repair, especially for the ointment containing 20% extract. Conclusion: Regarding the high content of phenolic compounds and flavonoids, besides potent antioxidant properties of the flowers of L. candidum, the use of its ointments led to significant decrease of burn wound area, suggesting that these extract ointments can treat burn wounds and improve the healing processes.